Mapping Global Research on Sustainability and SDGs in Chemistry Higher Education - Mellyzar; Marhami; Sirry Alvina; Sri Rahayu Retnowulan (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This paper examines how the Sustainable Development Goals (SDGs) have been brought into university-level chemistry education worldwide. Using a blend of bibliometric and systematic review methods, we analyzed 564 publications from Scopus and Web of Science (2001–June 2025), along with a closer look at 17 influential papers. Over the past twenty years, there’s been a clear uptick in studies on this topic, largely shaped by global education policies and sustainability initiatives. The United States, Canada, China, and the UK stood out as the most active contributors. Our findings reveal that green chemistry, systems thinking, and hands-on learning are key themes. Different teaching approaches, like problem-based and authentic learning, have helped improve students’ understanding of concepts, awareness of sustainability, and ethical outlook. Still, gaps remain, especially in how these ideas play out across cultures, their long-term effects, and how fully SDGs are woven into various chemistry programs. These insights point to the important role chemistry education can play in preparing graduates who are both scientifically grounded and ethically mindful. Looking ahead, future studies might benefit from broader data, longer-term designs, and cross-disciplinary efforts to keep pushing sustainable chemistry education forward.